THE ROLE OF LOCAL GOVERNMENT IN MAINTAINING COFFEE PRICES VOLATILITY IN GAYO HIGHLAND OF INDONESIA - Chairul Fahmi; Ahmad Luqman Hakim; Rahmi Putri Febriani; Laila Muhammad Rasyid (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2023)
During the Covid pandemic from 2019 until 2022, coffee prices in Gayo Highland have experienced multiple drops and high volatility. This study aims to investigate the role of the local government in maintaining the volatility of coffee prices in the Bener Meriah district of the Gayo Highland area. This study used data on coffee prices at the producer level, the planters and the reseller. o examine the local government policy and practice, we use the theory of Tas'ir al-Jabari. The results show that the local government has issued several policies to protect the planters' coffee prices, including activating the Warehouse Receipt System (WRS), conducting training and socialization on coffee management, and conducting coffee rehabilitation and rejuvenation programs. However, the local government's effort has yet to be maximized due to the lack of power of the local government to intervene over the price volatility. The prices are heavily influenced by supply and demand, as are the prices of other commodities. Therefore, the local government's policies for securing coffee prices have yet to be able to reflect the principles of at-Tas'ir Aljabari, in which the ruler has absolute authority to control and manage the market price of coffee beans in the Gayo Highland region. Abstrak: Selama pandemi Covid dari tahun 2019 hingga 2022, harga Kopi di dataran tinggi Gayo penurunan dan berfluktuasi. Penelitian ini bertujuan untuk mengetahui kebijakan pemerintah daerah dalam menjaga volatilitas harga di pasar lokal di wilayah Gayo. Penelitian ini menggunakan data harga kopi di tingkat produsen, pekebun dan reseller. Untuk mengkaji kebijakan dan praktik pemerintah daerah, kami menggunakan teori Tas’ir al-Jabari. Hasil penelitian menunjukkan bahwa pemerintah daerah telah mengeluarkan beberapa kebijakan dalam melindungi harga kopi pekebun, antara lain dengan mengaktifkan Sistem Resi Gudang (SRG), melakukan pelatihan dan sosialisasi pengelolaan kopi, melakukan program rehabilitasi dan peremajaan kopi. Namun, upaya pemerintah daerah belum maksimal karena kurangnya kekuatan pemerintah daerah untuk melakukan intervensi atas anjloknya harga biji kopi di pasar. Semua harga sangat dipengaruhi oleh penawaran dan permintaan. Oleh karena itu, kebijakan pemerintah daerah untuk mengamankan harga kopi belum mampu mencerminkan prinsip at-Tas’ir Aljabari, yang mana pemerintah mempunyai hak absolut untuk mengontrol harga pasar terhadap komoditas biji kopi diwilayah dataran tinggi Gayo. Kata kunci: Pemerintah Daerah, Jaga Harga Kopi, Volatilitas Di Dataran Tinggi Gayo